Extraordinary dust event over Beijing, China, during April 2006: Lidar, Sun photometric, satellite observations and model validation - Papayannis, Alexandros D.; Zhang, Huaiqing; Amiridis, Vassilis; Ju, Hongbo; Chourdakis, Giorgos; Georgoussis, Georgios; Pérez García-Pando, Carlos; Chen, Hongbin; Goloub, Philippe; Mamouri, Rodanthi-Elisavet; Kazadzis, Stelios; Paronis, Dimitrios; et al. (My University, 2007)
An extraordinary dust event over Beijing (April 2006) was followed by a synergy of lidar, Sun photometric and satellite measurements. Extreme aerosol optical depth (AOD) values (1-4) were measured by AERONET and MODIS over Beijing. The size distribution of the particles remained close to 2.5 μm and the single scattering albedo was around 0.92 ± 0.5 (440 nm). Coarse particles contributed to more than 60-80% to the AOD values, indicating the presence of very large particles (Ångström exponent <0.3). Coarse particle contribution to total AOD is associated with the free-tropospheric aerosols calculated by lidar profiles (65%). Lidar vertical profiles with AOD values from AERONET were used to estimate a typical lidar ratio for the dust particles (84 sr) during the most intense dust period. The DREAM forecast model was applied for the accurate description of the dust event evolution. Ground-truth data were used for the validation of DREAM over the Beijing area. Copyright 2007 by the American Geophysical Union.
Keywords: Aerosol; Dust; Dust aerosols